ANALISIS PENERAPAN APLIKASI SISKEUDES DALAM MENINGKATKAN KUALITAS AKUNTABILITAS KEUANGAN DESA DI DESA HUYULA - Gusasi, Sry Anita; Lantowa, Felmi D. (Program Studi Akuntansi, 2021)
This research aims to first analyze the management of the SISKEUDES application and analyze the application of the SISKEUDES application in improving the quality of village financial accountability in Huyula Village, Mootilangosub-district, Gorontalo regency. This research uses descriptive research with a qualitative approach. . Collecting data used descriptive research and qualitative approach The result of this research is that the management of the SISKEUDES application in Huyula Village, Mootilango sub-district, Gorontalo regency has carried out an accountability process according to established procedures. Huyula Village has also implemented the principle of obedience and obedience in carrying out duties and responsibilities. For the quality of financial accountability in Huyula Village, after the implementation of the SISKEUDES application, it brought quite a good change for the Huyula Village government, namely making it easier to report accurate accountability so as to produce transparent and accountable financial reports